RELEVANCE OF CLASSICAL MUSIC IN CINEMA MUSIC: सिने संगीत में शास्त्रीय संगीत की प्रासंगिकता - Rain, B. (International Journal of Research -GRANTHAALAYAH, 2015)
Indian scholars have considered music to be a divine voice. This entire universe is subject to nad, and nad is called Brahm, because nad is everywhere. This entire universe is foolish. Naad is composed of Brahman, Brahman with word, word by sentence and sentence by song, so it can be said that Naad is the soul of music. Harsh, gaiety, zeal, it is the makeup of a person's life, when the person becomes weak by getting entangled in social bonds or problems, then the arts in which the work of replenishing power and passion is there, they are called fine arts and fine arts. Music is considered to be the highest in the world. It would not be an exaggeration to say that man and music have an integral relationship. भारतीय विद्वानों ने संगीत को ईष्वरीय वाणी माना है। यह समस्त सृष्टि, नाद के अधीन है तथा नाद को ब्रह्म कहा गया है, क्योंकि नाद सर्वत्र व्याप्त है। यह सम्पूर्ण ब्रह्माण्ड ही नादमय है। नाद से ब्रह्म, ब्रह्म से शब्द, शब्द से वाक्य तथा वाक्य से गीत बनता है, अतः यह कहा जा सकता है कि नाद संगीत का प्राण है। हर्ष, उल्लास, उमंग, यह व्यक्ति के जीवन का श्रृंगार है, जब व्यक्ति सामाजिक बंधनों अथवा समस्याओं में उलझकर कमजोर होने लगता है, तब उसमें पुनः शक्ति तथा जोष भरने का कार्य जिन कलाओं में है, उन्हें ललित कलायें कहा जाता है और ललित कलाओं में संगीत का स्थान सर्वोच्च माना जाता है। यह कहना अतिष्योक्ति नहीं होगा कि मनुष्य तथा संगीत का अभिन्न सम्बन्ध है।8